The Effect of Curing Tip Contaminants and Curving Duration on the Depth of Cure of Resin Composites/Michael C. Siao. - Siao, Michael C.
Introduction. The effect of obstructions and barriers on the light curing tip and curing duration has already been previously investigated. However, there is little evidence on how they directly affect the depth of cure of resin composites. This study aimed to determine the effect of resin composite contaminants on the light curing tip and curing duration on the depth of cure of light cure resin composites.